Sharp Rise In Medicare Enrollees Being Held In Hospitals For Observation Raises Concerns About Causes And Consequences - Feng, Zhanlian; Wright, Brad; Mor, Vincent (Health Affairs, 2012)
When it is not clear that an ill patient needs to be hospitalized, he or she may be placed "under observation" in a hospital for further evaluation and short-term treatment. These hospital observation services, often a kind of halfway point between emergency department treatment and full inpatient admission, have become a hotly debated policy issue and subject of lawsuits. Using Medicare enrollment and claims data nationwide, we documented a rising trend in the prevalence and duration of hospital observation services in the fee-for-service Medicare population during 2007-09, accompanied by a downward shift in inpatient admissions. As a result, the ratio of observation stays to inpatient admissions increased 34 percent, from an average of 86.9 observation stay events per 1,000 inpatient admissions per month in 2007 to 116.6 in 2009. Medicare beneficiaries were increasingly subjected to hospital observation care and treated as outpatients instead of inpatients, which can expose them to greater out-of-pocket expenses if they are eventually admitted to skilled nursing facilities. Additionally, the nearly one million beneficiaries receiving observation services each year were, on average, being held in observation for a longer period of time per episode-some for longer than seventy-two hours. The prevalence of observation services varied greatly across geographic regions and hospitals. This may be an unintended consequence of Medicare payment policies designed to constrain hospital admissions. Additional research is needed to pinpoint the drivers and consequences of this phenomenon, as is more clarity in clinical practice and Medicare policy guidelines regarding observation care.